2004
DOI: 10.3727/000000004783983495
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Inhibits Fas-Mediated Apoptosis of Primary Mouse Hepatocytes in Culture

Abstract: Apoptosis occurs during the isolation and even short-term storage and culture of hepatocytes, and in the pathogenesis of liver diseases, such as hepatic failure and hepatitis. Therapeutic hypothermia has beneficial effects in experimental models of fulminant hepatic failure. The mechanisms underlying the potential benefits of mild hypothermia on the liver have not been well investigated. We examined the effects of temperature on soluble Fas ligand-induced apoptosis in freshly isolated mouse hepatocytes. Decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 45 publications
0
18
1
Order By: Relevance
“…Our observations with anti-Fas antibody contrast with results obtained in other cell types, such as freshly isolated hepatocytes and mouse fibroblasts, in which mild hypothermia blocked Fas-induced apoptosis without affecting activation of caspase 8 and cleavage of Bid [45,46]. This discrepancy could be cell type-specific or due to differences in the incubation temperature, 32 • C versus RT.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our observations with anti-Fas antibody contrast with results obtained in other cell types, such as freshly isolated hepatocytes and mouse fibroblasts, in which mild hypothermia blocked Fas-induced apoptosis without affecting activation of caspase 8 and cleavage of Bid [45,46]. This discrepancy could be cell type-specific or due to differences in the incubation temperature, 32 • C versus RT.…”
Section: Discussioncontrasting
confidence: 85%
“…This protective effect has been associated with elevated Akt activity [44]. In vitro, decreasing the culture temperature to 32 • C protects mammalian cells from apoptosis induced by various stimuli, including antiFas antibody [45,46]. Moreover, ex vivo handling of blood cells for conservation or manipulation and subsequent in vivo transplantation may expose cells to various thermal conditions that might compromise cell viability [47].…”
Section: Discussionmentioning
confidence: 97%
“…In 2004, Fu et al first evaluated the hepatocyte apoptosis with the treatment of mild hypothermia, and their research indicated that mild hypothermia (26℃) could suppress Fas-mediated apoptotic signaling pathways in liver cells. This function mainly depended on the inhibition of some signaling events, such as cytochrome c release, effector caspase activation, and so on [10]. In recent years, the protective effect of mild hypothermia was also evaluated in some other kinds of liver cell injury models to clarify more detailed mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that hypothermia reduces liver injury [164], [165] and [166], but it may impair liver regeneration [167]. Further research will be needed to clarify these issues.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%